Fontes de fósforo em rações orgânicas para alevinos e juvenis de tilápia do nilo (Oreochromis niloticus) - Dieterich, Fabiana (2010)
Two experiments were conducted in the Aquaculture Laboratory of the Group of Studies on Aquaculture Handling (GEMAq, in the Portuguese acronyms), which, by the way, belong to the State University of the West of Paraná, in Toledo. In experiment 1, we utilized 270 Nile tilapia fingerlings (Oreochromis niloticus) with 0.88±0.33g average weight, assigned into 18 500-liter tanks, in a total random fashion, indoor system. Each experiment dealt with three treatments and six repetitions, with a daily renewal of water equivalent to 10%, done through siphonage in order to eliminate feces and occasional feed rests. The fingerlings and the juveniles was feed organic, coming from corn, wheat and soybean meal, containing 32% and 28% of gross protein (GP), for the first and the second experiment, respectively. The diets were supplemented with industrial waste seafood flour (SF), bicalcium phosphate (BF), or their combination (SF + BF), in which case both the sources contributed with 50% of phosphorus amount. Physico-chemical parameters were evaluated (OD, pH, conductivity and temperature), as well as water analyses, one in the beginning, another after 30 days and a last one in 60 days of the experiment, aiming to check the values of ammonia, nitrite, phosphrus and nitrate. At the end of the experiment, then, the evaluations focused on livestock performance data and on the fish s carcasses chemical composition. Water physico-chemical parameters fit the recommendation for the species in both the experiments. Evaluated phosphorus sources didn t influence (P<0.05) livestock performance, or the carcass centesimal composition and the water quality for the raising of Nile tilapia fingerlings. For the juveniles of Nile tilapia fingerlings, the evaluated treatments did not bring a significant difference (p>0.05) as to the survival rate. However, there was a significant difference (p<0.05) for the final weight, the weight gain and the food conversion, what indicates that the fish feds with diets supplemented with bicalcium phosphate obtained low final weight and weight gain when compared to the fish fed with the diets supplemented with phosphorus coming from seafood flour and with phosphorus supplementation equally divided, 50% BF, 50% SF and a worse food conversion when compared with the treatment based on phosphorus coming only from SF, but it didn t differ (p>0.05) from the treatment SF and BF. The values obtained for phosphorus in water in experiments 1 and 2 were above the accepted by the resolution 357/2005 of CONAMA, what indicates the necessity of improvement in relation to the food handling and/or alternate treatment of the generated effluent. For fingerlings, it is either possible to use the bicalcium phosphate, seafood flour, or their combination as source of phosphorus. However, for Nile tilapia juveniles it is recommended to use the seafood waste meal as for the phosphorus supplementation, or also the combination of SF and BF (it is important to note that each source must supplement 50% of the phosphorus demands)